Derajat Miopia Berhubungan dengan Ketebalan Kornea Sentral pada Usia 18-40 Tahun - Elizabeth Ravinka Rossabel ER; Kartini Kartini (Jurnal Biomedika dan Kesehatan, 2022)
BackgroundThe central corneal thickness (CCT) is important in assessing the cornea’s condition and correlates with refractive errors in which myopic eyes have the thinnest central cornea. Based on the 2018 Riskesdas, 2,133,017 people suffer from severe low vision, of which 42% were connected to refractive errors. One of the treatments for myopia is to perform LASIK surgery, but complications may occur during its process. One of the risk factors for post-LASIK complications is a CCT of less than 500 microns. This study aimed to assess the association between the degree of myopia and CCT at 18-40 years old. MethodsThis study was a cross-sectional design with data taken from 124 medical records from the Gading Laser Eye Center with subjects aged 18-40 years consisting of 88 males and 36 females. Variables collected were initials, age, gender, CCT, and degree of myopia. Data analysis was carried out using the Chi-Square test with a significance level of p<0.05. ResultsThe age category was 18-28 (87.9%), dominated by males (71.0%). Most degrees of myopia were mild (48.4%), and CCT was dominated by thinning corneas (63.7%). Data analysis based on the Chi-Square test regarding the degree of myopia and CCT showed a significant association (p=0.001). ConclusionsThis study showed an association between the degree of myopia and CCT at the age of 18-40 years.